Variation of Gypsum Compound on Physical and Mechanical Properties of Lightweight Brick from Rice Husk - Arsita, Erra; Supriyadi, Asep; Sutandar, Erwin (Jurnal Teknik Sipil, 2024)
The construction development in Indonesia increases the demand for building materials, including lightweight bricks as wall materials. Recent innovations utilize natural materials, such as rice husk, as an alternative mixture that is environmentally friendly and can reduce the volume weight of lightweight bricks. This research uses gypsum compound as a cement substitute binder in a mixture of rice husk lightweight bricks to analyze the effect of variations in the use of gypsum on the physical and mechanical properties of lightweight bricks, as well as to determine the ideal percentage of gypsum compound and cement reduction. The research method used is experimental, with the manufacture of test specimens for visual testing, volume weight, water absorption, sound resistance, heat resistance, drying shrinkage, compressive strength, and split tensile strength. The mix composition used a volume ratio of 1 cement: 3 rice husk, with gypsum substitution of 0%, 35%, 40%, 45%, and 50%. The results showed that adding gypsum to lightweight bricks can accelerate the hardening process but reduce its physical and mechanical performance, such as decreasing compressive strength and increasing water absorption. Therefore, this research does not recommend using gypsum compound to manufacture rice husk lightweight bricks.